Panchayati raj institutionsayati raj institutions - Girglani J.M.
The author examines the various dimensions of raising resources by the panchayats and suggests certain measures for augmenting these resources, arguing in the process, against investing panchayats with powers to tax and mounting a plea for greater devolution of intire resources to the states from the centre, in order that the States may devolve more resources to the panchayati raj institutions
Keywords: Village Panchayats -- Finance -- India; Financial Institutions -- India